The plan of water and water ecosystem protection for Karelian Pyhäjärvi - Kukkonen, Minna; Kiiski, Jaana; Luotonen, Hannu; Niinioja, Riitta (North Karelia Regional Environment Centre, 2005)
Regional Environmental Publications 374 Karelian Pyhäjärvi is a valuable clear water lake located on the border between North Karelia (Finland) and the Republic of Karelia (Russia). It has been included in many national and international programs. It belongs also to the Finland’s nominations for the European Union nature protection network, Natura 2000, representing an oligotrophic habitat containing very few minerals characteristic of sandy plains. In 2002, a project was started and entitled “Assessment of the ecological state of an oligotrophic lake - as exemplified by the Transboundary Lake Pyhäjärvi on the Finnish-Russian Border”. This water protection plan is the first report of the project. It concentrates on the Finnish side of the border summarizing the average load in to the lake, water quality and ecological state of the lake and also water protection directions. The same type of water protection plan is underway for the Russian side. The annual nutrient load into Pyhäjärvi is about 12 000 kg phosphorus and 286 000 kg nitrogen. The main loading is caused by non-point sources. Anthropogenic impacts are mainly focused on the Finnish side of the lake. The load has decreased since the beginning of 1990s. Lake Pyhäjärvi represents an oligotrophic and clear water lake. Monitoring of the lake started in the 1960s and has been ongoing to the present. In the 1980s and 1990s, the water quality declined, (visibility impairment, algal blooms, sliming of fishing nets, increase of roach (carp and minnows?) in fish population) but during the last ten years, nutrient concentrations have decreased and the water quality increased. The aim of this water protection plan is to reduce the nutrient load especially from non point out puts, keep the conservation of the lake ongoing and strength the fish populations, especially vendace.